Jesus and the empire of God royal language and imperial ideology in the Gospel of Mark - Froelich, Margaret (London New York Oxford New Delhi Sydney T&T Clark, 2022)
"Margaret Froelich argues that the Gospel of Mark portrays the Kingdom of God as a conquering empire and Jesus as its victorious general and client king"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Kingdom -- Biblical teaching; Jesus Christ -- Royal office -- Biblical teaching; Bible -- Criticism, interpretation, etc